Enlarged housing space and increased spatial complexity enhance hippocampal neurogenesis but do not increase physical activity in mice - Funabashi, Daisuke; Tsuchida, Ryuki; Matsui, Takashi; Kita, Ichiro; Nishijima, Takeshi (Frontiers in Sports and Active Living, 2023)
Introduction Environmental enrichment (EE) improves various health outcomes, such as hippocampal neurogenesis, in rodents, which is thought to be caused, in part, by increased physical activity. However, the specific effect of each enrichment component, such as enlarged housing spaces and increased spatial complexity with a variety of objects, on physical activity remains unclear because of methodological limitations in measuring physical activity. We aimed to examine whether enlarged housing spaces and increased spatial complexity increase physical activity in mice using a body-implantable actimeter. Methods Adult male C57BL/6J mice were assigned to either standard housing or EE groups. The housing environment in the EE mice was gradually enriched by enlarging the housing space and the placement of a variety of objects. Physical activity was measured using a body-implanted actimeter. Hippocampal neurogenesis was immunohistochemically examined. Results Enlarged housing spaces and the placement of a variety of objects did not increase physical activity in mice. In contrast, hippocampal neurogenesis was enhanced in the EE mice, suggesting that environmental interventions successfully provided enriched housing conditions for these mice. Conclusions These results indicate that enlarged housing spaces and increased spatial complexity do not increase physical activity in mice. Furthermore, we found that EE enhanced hippocampal neurogenesis without increasing activity volume. Besides the current understanding that increasing the amount of physical activity is key to improving hippocampal function, our result suggests that the environment in which physical activity takes place is also a crucial contextual factor in determining the impact of physical activity on hippocampal function.